Sistem Pakar Diagnosa Penyakit pada Sapi Menggunakan Metode Rational Unified Process - Dimas Malik Suryanda; Jaroji Jaroji (Jurnal Penelitian Rumpun Ilmu Teknik, 2024)
Cattle are livestock that have economic potential. Alongside their significant economic potential, there is a considerable risk, namely diseases in cattle. Diseases in cattle can spread rapidly and can be fatal, leading to death. These diseases can be caused by bacteria, viruses, fungi, and parasites. To prevent the spread of diseases in cattle, cattle farmers must first be aware of the diseases in their livestock so that prevention and treatment can be carried out as early as possible. Using the Rational Unified Process (RUP), a expert system for diagnosing diseases in cattle is built to support this process. The expert system is constructed using the Random Forest Algorithm, with its implementation based on a website to provide quick and practical diagnostic results, offering information relevant to the type of disease.